THE INHIBITORY EFFECT OF BAMBOO CHARCOAL EXTRACT ON THE GROWTH OF STREPTOCOCCUS MUTANS - Sekarningrum, Galih Prawesty Ayu; Aminah, Siti; Jayanti, Lira Wiet; Anwar, Risyandi (Universitas Muhammadiyah Semarang, 2025)
ABSTRACTBackground: Streptococcus mutans is the primary cause of dental caries due to its acidogenic and aciduric properties. Natural antibacterial agents, such as bamboo charcoal extract, have been explored as potential alternatives to synthetic antimicrobial agents. However, the effectiveness of bamboo charcoal extract in inhibiting Streptococcus mutans remains uncertain. This study aimed to evaluate the antibacterial potential of bamboo charcoal extract at various concentrations.Methods: This research was conducted using a laboratory experimental method. The number of samples per group was determined using the Federer formula (t−1)(n−1)≥15, where t is the number of treatment groups and n the number of replications. With seven groups (six concentrations of bamboo charcoal extract and one positive control), a minimum of three replications per group was required, resulting in 21 samples in total. Bamboo charcoal extract was prepared through maceration using 96% ethanol and tested at concentrations of 0%, 12.5%, 25%, 37.5%, 50%, and 62.5% against Streptococcus mutans using the disk diffusion method. A 0.2% chlorhexidine solution served as the positive control. Inhibition zones were measured after a 24-hour incubation at 37°C.Results: Statistical analysis using descriptive analysis showed no significant difference in inhibition zones. None of the bamboo charcoal extract concentrations demonstrated antibacterial activity against Streptococcus mutans. In contrast, the positive control (0.2% chlorhexidine) produced a significant inhibition zone of 12.56 mm.Conclusion: Bamboo charcoal extract at concentrations of 12.5%, 25%, 37.5%, 50%, and 62.5% did not show any inhibitory effect on the growth of Streptococcus mutans.